Trends and Determinants of Condom Use Among Indonesian Adolescents: Evidence from 2007–2017 IDHS - Qatrannada, Shabrina Arifia; Shaluhiyah, Zahroh; Purnami, Cahya Tri (Journal of Population and Social Studies [JPSS], 2026)
Adolescent sexual and reproductive health remains a significant public health concern in Indonesia, particularly amid increasing reports of unprotected premarital sex. In 2022, adolescents accounted for approximately 50% of new HIV cases, underscoring the need for improved protection and education. This study aimed to examine trends in condom use among Indonesian adolescents from 2007 to 2017 and identify factors associated with protected sexual behavior. Data were drawn from three waves of the Indonesian Demographic and Health Surveys (IDHS) conducted in 2007, 2012, and 2017 using a two-stage stratified sampling design. Analyses included descriptive statistics and multivariable logistic regression. The proportion of adolescents reporting protected sex increased from 11.8% in 2007 to 20.6% in 2012, followed by a slight decline to 18.1% in 2017. HIV stigma was associated with a lower likelihood of condom use in 2017 (AOR = 0.75, 95% CI [0.57, 0.97]). Male adolescents had higher odds of condom use across survey years, as did adolescents residing in urban areas. Adolescents aged 18–24 and those with higher education showed increased odds of condom use in 2017. Exposure to condom-related information on television was consistently associated with higher odds of protected sex. In contrast, adolescents reporting sexual activity with non–sex workers had a lower likelihood of condom use in 2017 (AOR = 0.28, 95% CI [0.13, 0.70]). Although condom use has improved over time, its overall prevalence remains low. Strengthening comprehensive sexuality education and addressing structural and sociocultural determinants are essential to improve protective sexual behaviors among adolescents.